Price fairness evaluation on hotel online distribution channels, customers emotional and behavioural response / Wan Ahmad Nasroun Wan Salman - Wan Salman, Wan Ahmad Nasroun (2021)
Nowadays, hotels opt to promote their products or services in an online approach through their website. In order to increase the revenue and at the same time reduce the unsold rooms, hotels employ online intermediaries, such as Agoda, Booking.com, and Expedia. However, the emerging of online intermediaries has created a new challenge and issue on room price matters. Customers' perplexity on hotel room price leads to fairness evaluation. Therefore, the aim of this study is to examine customers' price fairness evaluation on hotel online distribution channels towards their emotions and behavioural response. Price fairness was assessed by distributive fairness (the price advertised) and procedural fairness (organizations that set the price), as grounded in social comparison theory. In order to gain a deeper understanding of customers' price fairness evaluation, a quantitative longitudinal survey was adopted. A total of 48 postgraduate students employed in this study, which involved five different periods of assessment. The data collected begins from 28 days prior to check-in until the check-in day, with seven days gaps on each assessment period. The Structure Equation Modelling-Partial Least Square (SEM-PLS) used to analyse the results. Findings showed that customers rate the hotel as fair for both fairness dimensions (distributive and procedural), at the initial stage of the investigation. However, when closer to the check-in day, customers mostly concerned on the price posted (distributive), compared to the organization that set the price (procedural). Customers' emotional and their behavioural response was also examined based on fairness dimensions. The results indicated that fair price leads to positive emotions, so as positive behavioural responses. This study extends current price fairness research, especially in the hotel industry. In the academic perspective, the needs to explore both dimensions of fairness deemed as necessary in broadening the knowledge in psychological and behavioural research. On the other hand, hotel managers may use these findings to understand customers' behaviour, particularly in price fairness evaluation.